2008
DOI: 10.1186/1471-2148-8-321
|View full text |Cite
|
Sign up to set email alerts
|

Suprafamilial relationships among Rodentia and the phylogenetic effect of removing fast-evolving nucleotides in mitochondrial, exon and intron fragments

Abstract: BackgroundThe number of rodent clades identified above the family level is contentious, and to date, no consensus has been reached on the basal evolutionary relationships among all rodent families. Rodent suprafamilial phylogenetic relationships are investigated in the present study using ~7600 nucleotide characters derived from two mitochondrial genes (Cytochrome b and 12S rRNA), two nuclear exons (IRBP and vWF) and four nuclear introns (MGF, PRKC, SPTBN, THY). Because increasing the number of nucleotides doe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
87
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(105 citation statements)
references
References 74 publications
16
87
2
Order By: Relevance
“…The monophyly of anomaluromorphs was recently confirmed by DNA sequences (Montgelard et al, 2008;Blanga-Kanfi et al, 2009). Nine extant species are currently recognized in the suborder.…”
Section: Anomaluromorphamentioning
confidence: 89%
“…The monophyly of anomaluromorphs was recently confirmed by DNA sequences (Montgelard et al, 2008;Blanga-Kanfi et al, 2009). Nine extant species are currently recognized in the suborder.…”
Section: Anomaluromorphamentioning
confidence: 89%
“…The squirrel-related clade is characterized by different types of locomotion [31,32] and comprises the families Sciuridae, Aplodontidae and Gliridae [33][34][35][36]. The relationship between these three families is contradictory and subject of many morphological (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Some have argued that phiomorphs and caviomorphs are likely to have shared a common Afro-Arabian ancestor (15)(16)(17), while others have suggested that the phiomorph-caviomorph split might have occurred in Asia, and that caviomorphs dispersed to South America either through Afro-Arabia or via a southern Gondwanan route (13,18). One critical issue that has hindered understanding of the group's historical biogeography is the phylogenetic position of the family Hystricidae, which has been placed as either the sister group of a phiomorph-caviomorph clade or as the sister group of Caviomorpha, in recent molecular phylogenetic analyses (9,(19)(20)(21). Temporal and tectonic constraints on competing biogeographic hypotheses have also been limited by radically different molecular estimates of the phiomorph-caviomorph split, which range in age from Ϸ85 Ma to Ϸ36 Ma (9,18,19,22,23).…”
mentioning
confidence: 99%